Hemorrhage in pelvic ring fractures after low-energy trauma: a systematic review - Rossler, Alina; Lukhaup, Lara; Seidelmann, Max; Gaeth, Catharina; Dietz, Sven-Oliver; Audretsch, Christof; Grützner, Paul Alfred; Windolf, Joachim; Neubert, Anne (Journal of Clinical Medicine, 2024)
Background/Objectives: The aim was to investigate diagnostic, treatment and preventive options to establish an overview of the existing evidence on hemorrhage in pelvic fractures in older adults. Methods: A systematic review was conducted. Due to the rarity of this complication, only case reports and series with individuals older than 55 years with a pelvic ring fracture that is caused by a low-energy trauma or no apparent trauma, along with hemorrhage, were eligible. A search was performed on four databases. The CARE checklist was used to investigate the reporting integrity of the included studies. Analysis was performed narratively, and this study was registered on the Open Science Framework. Results: 21 patients from 19 studies were included (17 females and 4 males) with an average age of 82.1 years. The 21 patients suffered a total of 29 fractures. Pubic ramus fractures were present in 48.3% of all fractures. In 42.9%, an active hemorrhage was reported. Arterial vessels were injured in direct anatomical relationship to the fracture. Abdominal pain and hemorrhagic instability were the main red flag symptoms reported. Active arterial hemorrhage was diagnosed by CT with angiogram and treated by embolization with or without additional surgery. Conclusions: Clinically relevant hemorrhage in pelvic fractures due to low-energy trauma is rare. However, these fractures, combined with clinically relevant hemorrhage, account for an increased mortality and morbidity in elderly people. This systematic review was able to create a clinical decision tree for hemorrhage in ramus pubic fractures.
Gesehen am 06.05.2025